2017
DOI: 10.1002/chem.201704037
|View full text |Cite
|
Sign up to set email alerts
|

Atmosphere‐Controlled Chemoselectivity: Rhodium‐Catalyzed Alkylation and Olefination of Alkylnitriles with Alcohols

Abstract: The chemoselective alkylation and olefination of alkylnitriles with alcohols have been developed by simply controlling the reaction atmosphere. A binuclear rhodium complex catalyzes the alkylation reaction under argon through a hydrogen‐borrowing pathway and the olefination reaction under oxygen through aerobic dehydrogenation. Broad substrate scope is demonstrated, permitting the synthesis of some important organic building blocks. Mechanistic studies suggest that the alkylation product may be formed through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
58
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 53 publications
0
58
0
Order By: Relevance
“…Screening of reaction temperature and time showed that 120°C and 24 h were optimal (Table 1, entries 12-15). Next, we screened solvents including xylene, NMP, DMF, dioxane, nBu 2 O and the mixed solvents of toluene and NMP in different ratios and the results showed that a 1 : 1 mixture of toluene and NMP was optimal for this transformation (Table 1, entries [16][17][18][19][20][21][22][23]. The existence of NMP might increase solubility of NaOtBu and formed secondary alcoholates in the mixed solvent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening of reaction temperature and time showed that 120°C and 24 h were optimal (Table 1, entries 12-15). Next, we screened solvents including xylene, NMP, DMF, dioxane, nBu 2 O and the mixed solvents of toluene and NMP in different ratios and the results showed that a 1 : 1 mixture of toluene and NMP was optimal for this transformation (Table 1, entries [16][17][18][19][20][21][22][23]. The existence of NMP might increase solubility of NaOtBu and formed secondary alcoholates in the mixed solvent.…”
Section: Resultsmentioning
confidence: 99%
“…Reaction of secondary/tertiary benzylic or allylic alcohols with trialkylsilyl cyanide and oxidation conversion from primary alcohols and ammonia represents direct synthetic methods of nitriles. [12] The α-alkylation of nitriles with primiary alcohols was well established which could be catalyzed by precious metals such as Ru, [13] Os, [14] Pd, [15] Rh [16] and Ir, [17] and earth-abundant metals such as Mn [18] and Fe. [19] It is rare to see α-alkylation reaction of nitriles with secondary alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Complex 20 also showed a high catalytic activity with respect to the chemoselective alkylation and olefination of alkylnitriles with alcohols . Remarkably, the outcome of the reaction could simply be controlled via the reaction atmosphere: The alkylation product was formed under inert conditions (Ar atmosphere; whereas, the presence of O 2 strongly favored the formation of the olefination product (Scheme ).…”
Section: Terpyridine Complexes As Catalysts For Organic Reactionsmentioning
confidence: 99%
“… Schematic representation of the alkylation and olefination of nitriles by primary alcohols, catalyzed by 20 . Figure reproduced with kind permission; © 2017 Wiley‐VCH.…”
Section: Terpyridine Complexes As Catalysts For Organic Reactionsmentioning
confidence: 99%
“…Since 1981, when Grigg and co‐workers first used RuH 2 (PPh 3 ) 4 as a catalyst in the alkylation of nitriles with alcohol, a lot of effort has been devoted to exploring various catalysts, including Ru, Rh, Ir, Pd, Os, Fe, and Mn. Of these, Ru complexes are the most reported, for example Gunanathan's group reported that Ru(PNP) (PNP = bis(2‐(diphenylphosphino)‐ethyl)amine) pincer complex showed good activity for α ‐alkylated reaction of arylmethyl nitriles .…”
Section: Introductionmentioning
confidence: 99%